Respuesta :

Answer:

(-9, -26)

Step-by-step explanation:

y = (x - 1)2 - 6 and y = 4x + 10

Since they are both y =, you can set the two equations equal to each other:

(x - 1)2 - 6 = 4x + 10

2x - 2 - 6 = 4x + 10

-2 - 6 = 2x + 10

-8 = 2x + 10

2x = -18

x = -9

Check:

y = (x - 1)2 - 6

y = (-9 - 1)2 - 6

y = -18 - 2 - 6

y = -26

y = 4x + 10

y = 4 (-9) + 10

y = -36 + 10

y = -26

The answer to these equations is (-9, - 26). If you graph this, this is the point where the two graphs intersect.

Ver imagen eyestrane